Lao Economic Monitor, April 2015 : Towards Restoring Macroeconomic Stability and Building Inclusive Growth - Phimmahasay, Keomanivone (World Bank, Vientiane, 2015)
Based on preliminary estimates, the Lao People's Democratic Republic (PDR) economy grew by 7.5 percent in 2014, compared to an average of 8 percent over 2011-13. Looking forward, real gross domestic product (GDP) growth is projected to slow further in 2015 before accelerating in the medium term. Average annual inflation in 2014 decelerated to 4.2 percent from 6.4 percent a year earlier, driven primarily by slower growth in food prices and a decline in fuel prices. In response to a widened fiscal deficit in FY2012-13, the government embarked on much needed fiscal corrective measures in FY2013-14 and FY2014-15. Foreign exchange reserves coverage remains low as compared with prudential benchmarks. While the nominal exchange rate remained relatively stable within the band set by the Bank of Laos (BOL), the real exchange rate continued to appreciate. Indications in 2014 are that bank credit growth is slowing down sharply compared to its previous rapid pace over several years. In order to grasp new opportunities and enjoy the benefits of regional integration, it is necessary for Lao PDR to take steps to create a conducive business environment. In order to achieve broad-based, inclusive growth and poverty reduction in Lao PDR, channeling greater resources toward tackling key workforce skills and productivity challenges is of significant importance.